A MODEL FOR DEVELOPING STUDENTS’ COMMUNICATIVE COMPETENCE BY TEACHING THEM INTERCULTURAL COMMUNICATION - Paziljanova Zulfiya Sabirjanovna (Galaxy International Interdisciplinary Research Journal, 2022)
Communicative competence is an essential part of teaching so the purpose of the article is to illustrate a model for developing students’ communicative competence by teaching them intercultural communication with a hope adding a little contribution to the linguistics and teaching